Study on Utilization of Active Natural Zeolite as Ammonia Absorbent in Aquarium as a Medium Fresh Fish Cultivation - Chairuddin; Marbun, Roberta; Gulton, Jamahir (Talenta Publisher, 2022)
A study of the use of natural zeolite active as ammonia absorbent in an aquarium as the cultivation of medium fresh fish has been conducted. The water sample was taken from the surface water of Toba Lake, Pangururan, Samosir Regency. Natural zeolite was refined until measured at 200 mesh and activated by physics. Determination of ammonia was performed using spectrophotometrically with the Nessler method at the maximum wavelength of 410 nm. The result of the analysis of this study obtained that decrease in water pH and ammonia content in the water after feeding the fish was caused by the absorption of active natural zeolite active to the tenth day which concentration of ammonia on the first and tenth day was 1.2723 mg/L and 2.4171 mg/L with the largest absorption percent on the day to ten was 38.04%.